Penicillium sinense, a new species of endophytic fungi from Citrus trifoliata with inhibition activities to pathogenic fungi - Li, Xin; He, Xiulan; Shi, Weixiong; Zuo, Shuyu; Li, Xue; Peng, Di; Guo, Zhaohui; Su, Lei (Phytotaxa, 2025)
Penicillium is a common, widespread and economically important genus. In an investigation of endophytic Penicillium species associated with trifoliate orange in China, a novel species in Penicillium section Exilicaulis, namely P. sinense was isolated from the leaves of Citrus trifoliata L. in Changsha, Hunan, China. It is different from other Penicillium species morphological comparisons and phylogenetic analyses. Multi-locus (CaM, ITS, RPB2 and TUB) phylogenetic analysis confirmed that P. sinense is distinct from other species. A synopsis of the morphological characters of the new species is provided. The biocontrol potential of P. sinense was measured by the confrontation test between P. sinense and common pathogenic fungi. The results of the study provided a strain resource for screening effective antagonistic Penicillium strains and biological control of fungal diseases.